Mengadili Politik Uang: Peran DKPP - Fedila Wica Tsabitah; Intan Nuraini (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The practice of money politics remains a serious challenge in the implementation of the 2024 General Election and the 2024 Regional Elections in Indonesia, as it has the potential to undermine the principles of fairness, honesty, and democratic integrity. This study aims to analyze the role of the Election Organizer Ethics Council (DKPP) in adjudicating violations related to money politics, particularly from the ethical perspective of election organizers. The method used is a qualitative approach through literature study of laws, regulations, and DKPP decisions. The findings indicate that DKPP plays a strategic role in maintaining the neutrality and professionalism of election organizers by enforcing the code of ethics, imposing sanctions, and supervising behaviors that may involve or tolerate money politics practices. Although DKPP's authority is limited to the ethical domain and does not extend to criminal law enforcement, its existence remains crucial as a moral guardian within the electoral system. Therefore, synergy between DKPP, law enforcement institutions, and public participation is necessary to minimize money politics and to realize democratic and integrity-based elections.